Bothriochloa laguroides ssp laguroides (D.C.) Herter biometric characterization, for a sustainable grazing management (Semiárida, 2020)
Grasses morphological knowledge, in space and time, is important in agronomic management actions. Bothriochloa laguroides is a key species in the grasslands of the hills region by higher prevalence of high forage value. The objective was to establish management guidelines to define more precisely the grazing intensity for that species. In a area of 95 ha, grazed breeding farm, were placed randomly distributed 4 closures. In every closing we selected 5 individuals of that species and every 7 days was measured total plant height (AT) and the height of the peduncle of the inflorescence visible (APVI) in both vegetative and reproductive stage. According to the results obtained showed that the growing period was maintained until mid-January. The start, peak and end of flowering occurred in midJanuary, late February - early March and late April respectively. On the other hand, there was a significant positive correlation (R = 0.8, α = 0.05) between AT and APVI. As a result, it could be recommend that grazing in the vegetative stage is of low intensity to favor the formation of bunches. From mid-January, when starts the reproductive stage, grazing may be of greater intensity until early March which should remove the animals. This manage ment would have a large supply of biomass to ensure the perpetuity of the species in time.
Keywords: Bothriochloa laguroides; Grazing intensity; Grassland hills; South of Córdoba Province